Study on the Influence of Low-Level Jet on the Aerodynamic Characteristics of Horizontal Axis Wind Turbine Rotor Based on the Aerodynamics–Controller Interaction Method - Pan He (Energies, 2022)
Accurate prediction of the aerodynamic characteristics of wind rotors subjected to various wind profiles is of considerable importance in the aerodynamics and structural design of wind turbines. As a very complex atmospheric phenomenon, the impact of a low-level jet (LLJ) on the aerodynamic characteristics of wind rotors is becoming more and more significant with the increase in wind turbine height. Additionally, during calculating the aerodynamic characteristics of the wind rotor, the known wind speed, rotor speed, and blade-pitch angle are generally required. However, when the wind profile is in the LLJ condition, it is difficult to determine the blade-pitch angle and rotor speed. Therefore, in this paper, the blade-element-momentum (BEM) method is exploited by considering the coupling with the generator-torque controller and blade-pitch controller. In order to solve the problem of the unknown rotor speed and blade-pitch angle under the LLJ condition, a C++ code is developed. Then, the influence of the LLJ on the aerodynamic characteristics of the wind rotor is exclusively examined. The research results show that the calculation method can precisely evaluate the rotor speed, blade-pitch angle, and aerodynamic characteristics of the wind rotor. The influence of the LLJ on the aerodynamic loads of the wind rotor is greater than that of the wind shear. When the LLJ is placed inside the rotor swept area, the aerodynamic loads of the blade exhibit two local maximums and local minimums with the variation of the azimuth angle in a rotation period. The closer the LLJ height is to the hub height, the greater the average aerodynamic loads of the wind rotor are, and the smaller the amplitude of aerodynamic loads of the blade is relative to the average value. When the LLJ height is positioned outside the rotor swept area, the change law of the aerodynamic loads of the blade would be similar to that of the wind subjected to a very strong wind shear inflow. This study provides a crucial reference for a more rational assessment of the aerodynamic characteristics of wind turbines under the action of complex wind profiles, as well as revealing the influence of the LLJ on the aerodynamic characteristics of wind turbines.